Do novice and experienced rowers adopt different pacing strategies and do their physiological and metabolic responses show optimisation? - López-Sánchez, G. F.; Smith, L.; Díaz-Suárez, A.; Towner, A.; Gordon, D. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The aim was to evaluate the pacing strategies and metabolic and physiological responses of novice and experienced rowers, over a 2000m racing profile. The sample was composed of 7 male university and town boat club rowers, 5 of which were novice (age 22.4±2.6 yr, height 182.6±8.4 cm, mass 79.7±8.9 kg), and 2 experienced (age 23.0±4.2 yr, height 194.1±4.1 cm, mass 90.3±2.0 kg). All participants performed a 2000m racing profile on the rowing ergometer followed by 3 trials in randomised order (500m, 1000m, 1500m) at the stroke rate and split time set from the original 2000m test. The last session consisted of a 2max test. During these tests, gas exchange, haematology, heart rate, split times, stroke rate and distances were recorded. Blood lactate (BLa) accumulation in novice rowers was continuously increased and plateaued in the final 500m quarter. Whereas, experienced rowers gradually increased in lactate accumulation, but maintained in the third quarter (1000-1500m) which allowed room for further accumulation in the final quarter (1500-2000m). The volume of oxygen uptake ( 2) increased linearly until the final 500m quarter for the experienced group, while novice rowers fluctuated throughout the time trial. In terms of pacing, the novice rowers followed an expected “all-out” strategy whereas, unexpectedly, the experienced rowers continuously dropped in speed until the mid-point (1000m) where they maintained a speed of 5.10m.s-1. The current findings suggest that at a physiological and metabolic level, the experienced rowers are more adapted to the demands of rowing a 2000m race. However, it appears that they do not always follow a “J-Shaped” strategy.